Kenya: Kenya Agricultural Commodity Exchange (KACE) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Kenya Agricultural Commodity Exchange (KACE) was launched in 1997 to provide reliable and timely market information on commodity types, supply, demand, and prices to guide and enhance private sector participation in more efficient production and marke